Reliability of instruments that measure situation awareness, team performance and task performance in a simulation setting with medical students. Issue 9 (12th September 2019) - Hultin, Magnus; Jonsson, Karin; Härgestam, Maria; Lindkvist, Marie; Brulin, Christine
Abstract : Objectives: The assessment of situation awareness (SA), team performance and task performance in a simulation training session requires reliable and feasible measurement techniques. The objectives of this study were to test the Airways–Breathing–Circulation–Disability–Exposure (ABCDE) checklist and the Team Emergency Assessment Measure (TEAM) for inter-rater reliability, as well as the application of Situation Awareness Global Assessment Technique (SAGAT) for feasibility and internal consistency. Design: Methodological approach. Setting: Data collection during team training using full-scale simulation at a university clinical training centre. The video-recorded scenarios were rated independently by four raters. Participants: 55 medical students aged 22–40 years in their fourth year of medical studies, during the clerkship in anaesthesiology and critical care medicine, formed 23 different teams. All students answered the SAGAT questionnaires, and of these students, 24 answered the follow-up postsimulation questionnaire (PSQ). TEAM and ABCDE were scored by four professionals. Measures: The ABCDE and TEAM were tested for inter-rater reliability. The feasibility of SAGAT was tested using PSQ. SAGAT was tested for internal consistency both at an individual level (SAGAT) and a team level (Team Situation Awareness Global Assessment Technique (TSAGAT)). Results: The intraclass correlation was 0.54/0.83 (single/average measurements) for TEAM and 0.55/0.83 for ABCDE. According to the PSQ, the items in SAGAT were rated as relevant to the scenario by 96% of the participants. Cronbach's alpha for SAGAT/TSAGAT for the two scenarios was 0.80/0.83 vs 0.62/0.76, and normed χ² was 1.72 vs 1.62. Conclusion: Task performance, team performance and SA could be purposefully measured, and the reliability of the measurements was good.